Startup ecosystem of Belarus: entrepreneurial intentions of the student youth - Pinchuk, Igor V.; Pokhomova, Alesya A.; Filinskaya, Larisa V. (Journal of the Belarusian State University. Sociology, 2026)
The article is devoted to the ecosystem of the startup movement in the Republic of Belarus in the context of entrepreneurial intentions and opportunities of students. The concept of a startup ecosystem and its elements are defined. The article analyses the results of a sociological study of Belarusian students conducted in 2024 in 10 institutions of higher education of the Republic of Belarus by the Public Opinion research cluster of the Belarusian State University (hereinafter referred to as the BSU Management Committee) on the initiative of the Secretariat of the Supervisory Board of the Hi-Tech Park. It is noted that universities play an important role in the functioning of the startup ecosystem and increasing the attractiveness of entrepreneurship among young people, the activities of startup centers in the structure of higher education institutions contribute to the development of innovative entrepreneurship as strategically important for the country’s economy. The results obtained can be applied in the development of measures for the further development of the startup movement in the Republic of Belarus, as well as the formation of a developed national startup ecosystem.
Keywords: student youth; entrepreneurial intentions; entrepreneurial culture; startup; startup ecosystem; startup centres; entrepreneurial university